CryoSeek II: Cryo-EM analysis of glycofibrils from freshwater reveals well-structured glycans coating linear tetrapeptide repeats - Tongtong Wang; Wenze Huang; Kui Xu; Yitong Sun; Qiangfeng Cliff Zhang; Chuangye Yan; Zhangqiang Li; Nieng Yan (Proceedings of the National Academy of Sciences, 2025)
Despite the recent breakthrough in structure determination and prediction of proteins, the structural investigation of carbohydrates remains a challenge. Here, we report the cryo-EM analysis of a glycofibril found in the freshwater in the Tsinghua Lotus Pond. The fibril, which we name TLP-4, is made of a linear chain of tetrapeptide repeats coated with >4 nm thick glycans. In each repeat, two glycans are O-linked to a 3,4-dihydroxyproline and another glycan attaches to the adjacent Ser or Thr. The fibril structure is entirely maintained through glycan packing. Bioinformatic analysis confirms the conservation of the TLP-4 repeats across species, suggesting the existence of a large number of glycofibrils to be discovered. Our findings not only provide valuable insights into the structural roles of glycans in bio-assemblies but also demonstrate the potential of our recently formulated research strategy of CryoSeek to find bioentities and establish prototypes for structural studies of carbohydrates.